An Industrial systems design study on Baggage Express Service and Transport, Inc. - Alombro, Kevin; Cardenas, Dorothy Patricia; Gonzalez, Noelle; Po, Marie Therese (Diliman, Quezon City College of Engineering, 2002)
Since the middle of the 20th century, commercial air transport has been the most common form of long-distance travel. Numerous airlines based in several different countries transport millions of people every year to various destinations around the world. Due to the complexity of operations systems of airlines, it is inevitable that some glitches may be present in these systems. One major aspect of operations wherein airlines encounter problems is that of transporting the baggages of their passengers from country to country. In most flights, the misplacement of baggages of passengers is usually unavoidable. The subject, Baggage Express Service and Transport Incorporated or BEST Inc., will immensely benefit from the application of Industrial Systems Design and other Industrial Engineering techniques. The company is relatively new, having been established five years ago. The company is among the first of its kind but currently faces intense competition. BEST Inc.?s operations focus on handling delayed baggage and controlling and delivering company mail for airlines at the Ninoy Aquino International Airport. Being a business of service, trustworthiness and operations efficiency of the company are the main requirements for the business to continue. To be competitive, BEST Inc. must streamline its operations. Each component in the system of operations should be well defined. The company must pay special attention to its operating costs and ensure consistent efficiency in its service. It must clearly define and focus its competitive priorities on areas critical to its business success. To stay in business, the company is looking into ways by which it can improve its productivity and reformulate the company?s strategy to address issues in the target market. Eventually, suggestions will be made on how to improve the utilization of the company?s resources more effectively. Furthermore, tools in operations management, operations research and industrial systems design will be used to help achieve the strategic goals of the company, the most important of which is to provide good service for its clientele. The paper will proceed within the framework set by the rationale and strive to achieve the realization of the goals outline in the objectives of the study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Baggage Express Service and Transport (BEST), Inc; Express service; Postal service; System design